Gender and Rural Non-Farm Entrepreneurship - Costa, Rita; Rijkers, Bob (Washington, DC: World Bank, 2012)
Using novel matched household-enterprise-community datasets from Bangladesh, Ethiopia, Indonesia and Sri Lanka, this paper analyses gender differences in rural non-farm entrepreneurship. Women have lower rates of non-farm entrepreneurship, except in Ethiopia. Female-headed households which run a non-farm firm derive a larger share of their income from it, even though female firms are smaller and less productive. Differences in output per worker are overwhelmingly accounted for by sorting by sector and size, as well as differences in factor intensity They are not due to, increasing returns to scale, differences in human capital or local investment climate characteristics. By contrast, gender differences in investment and growth rates are small.